Understanding the role of pressurized CO2 in the direct recycling process of Li-ion battery positive electrode - Neil Hayagan; Pierre Guillou; Jacob Olchowka; Fatma Ercicek; Carole Lecoutre; Olivier Nguyen; Cyril Aymonier; Samuel Marre; Arnaud Erriguible; Gilles Philippot (Journal of CO2 Utilization)
The ternary mixture of carbon dioxide (CO2), triethyl phosphate (TEP), and acetone enabled an efficient delamination of Li-ion battery (LIB) positive electrode inciting an interest to study the ternary mixture behavior. Pressurized fluids, such as CO2, are known to be beneficial in various chemical processes. However, the behavior of CO2, when mixed with TEP and acetone is not well understood, particularly under pressure and temperature conditions. This study investigates the behavior of CO2 or nitrogen (N2) in mixtures with TEP and acetone at various compositions, using experimental investigations of the ternary system. Experimental data covers four temperatures at 35°C, 70°C, 100°C and 120°C at a constant pressure of 100 bar. The phase behaviors of the binary and ternary mixtures were observed using a transparent reactor, while the compositions were analyzed in situ with Raman spectroscopy. Under isobaric conditions, a single phase was observed with CO2 at 35°C, both in the binary systems with either TEP or acetone, as well as in the ternary mixture. In contrast, a biphasic system was observed at higher temperatures (70°C, 100°C, and 120°C) in all mixtures containing CO2. Specifically, the biphasic condition at 55°C at 100 bar, of the mixtures were semi-quantitatively investigated using Raman spectroscopy to probe the compositions in the vapor and liquid phases. These observations elucidate the crucial role of CO2 in the delamination of the positive electrode in LIB using the TEP-acetone-CO2 system enabling high efficiency, low solvent consumption, and a faster processing time.